Comparative analysis of sixteen active compounds and antioxidant and anti-influenza properties of Gardenia jasminoides fruits at different times and application to the determination of the appropriate harvest period with hierarchical cluster analysis. (6th April 2019) - Shan, Ming-Qiu; Wang, Tuan-Jie; Jiang, Yu-Lan; Yu, Sheng; Yan, Hui; Zhang, Li; Wu, Qi-Nan; Geng, Ting; Huang, Wen-Zhe; Wang, Zhen-Zhong; Xiao, Wei
Abstract: Ethnopharmacological relevance: Gardenia jasminoides fruit (GJF) is used as a well-known traditional folk medicine, a food and a natural colorant in Asia with a long history. The herbal medicine has usually been harvested in the autumn from September to November. However, this time span is too long and might result in the quality instability of GJF. Aim of study: We aimed to conduct the comprehensive quality evaluation of GJF including the quantitative analysis of the bioactive components and the main bioactivities, and further to determine the most appropriate harvest time of this phytomedicine. Materials and methods: In this study, an UFLC-Q-TRAP-MS/MS method was established to quantify 7 iridoid glycosides (geniposide, geniposidic acid, secoxyloganin, gardenoside, genipin 1-gentiobioside, scandoside methyl ester, and shanzhiside), 7 phenylpropanoid acids (chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid, isochlorogenic acid A, isochlorogenic acid B, isochlorogenic acid C, and caffeic acid) and 2 carotenoids (crocin-1 and crocin-2) in GJF. With this method, nine samples of GJF harvested at different times were analyzed and compared. These samples were also investigated and compared in terms of their antioxidant activity (DPPH free radical scavenging, ABTS free radical scavenging, ferric-reducing antioxidation) and anti-influenza activity (neuraminidase inhibition), which are closely related to the GJF efficacies. Then, hierarchical cluster analysis (HCA) was separately performed for the quantitative analysis and bioactivity evaluation in vitro. Results: The HCA results demonstrated that three GJF samples (S5, S6, and S7) were clustered into one group for both quantitative analysis and bioactivity evaluation in vitro; these three samples were found to have the highest standardized scores in both the former (12.775, 12.106, 10.817) and the latter (3.406, 3.374, 3.440). Based on the comprehensive results, the optimum harvest period was confirmed to extend from mid-October to early-November. Conclusions: This study firstly validated the use of UFLC-Q-TRAP-MS/MS method for the determination of 16 bioactive components in GJF. It was also the first time that a quantitative analysis and a bioactivity assay in vitro were integrated for the determination of the most appropriate harvest period of GJF. We hope this paper may provide some reference to studies of appropriate harvest periods and even the quality control of TCMs. Graphical abstract: fx1